Changes in travel behavior during the transition from secondary to higher education: A case study from Ghent, Belgium - De Paepe, Leen; De Vos, Jonas; Van Acker, Veronique; Witlox, Frank (Journal of Transport and Land Use, 2018)
Over the past few decades, the number of students attending universities and university colleges in Belgium has increased considerably. In many Western countries, this trend is accompanied by a decline in car use among young adults. Therefore, it is important to have better insights into how travel behavior changes during the transition from secondary to higher education. This research fits into the larger framework of mobility biographies, where travel behavior is analyzed over a life course, taking into account certain life events. Hierarchical logistic regressions are used to analyze car use data for mandatory activities (going to school and grocery shopping) and leisure activities (fun shopping) of 404 first-year university and university college students in Ghent (Belgium). The results indicate that holding a driver’s license or owning a car facilitates car use irrespective of students’ residential location and lifestyle, and this is true for all activities. The built environment only seems to become an important factor explaining car use when students are attending university or university college. The influence of lifestyles appears to become somewhat more important for leisure activities, such as fun shopping. The emerging lifestyle of students appears to become more individual and more independent from the lifestyle of others, especially the parents. This is supported by the declining influence of social networks, notably the family.